Acclimation and adaptation to irradiance in symbiotic dinoflagellates. II. Response of chlorophyll-protein complexes to different photon-flux densities - Iglesias-Prieto, R.; Trench, R. K. (Marine biology, 1997)
The response of chlorophyll-protein complexes to super- and sub-saturatin -flux densities photon, PFD (250 mu mol quanta m-2 s-1 and 40 mu mol quanta m-2 s-1, respectively) were analyzed for Symbiodinium microadriaticum Freudenthal, the symbiont of the Caribbean jellyfish Cassiopeia xamachana; S. kawagutii Trench and Blank, the symbiont of the Indo-Pacific scleractinian Montipora verrucosa; and S. pilosum Trench and Blank,the symbiont of the Carribbean zoanthid Zoanthus sociatus.